Comprehensive strategy to design highly ordered mesoporous Nafion membranes for fuel cells under low humidity conditions - Zhang, Jin; Li, J.; Tang, H.; Pan, M.; Jiang, San Ping (R S C Publications, 2014)
A comprehensive strategy has been developed to synthesize highly ordered mesoporous Nafion membranes with different structure symmetries including 2D hexagonal (2D-H), 3D face-centered (3D-FC), 3D cubic-bicontinuous (3D-CB) and 3D body-centered (3D-BC), using a soft template method with the assistance of a silica colloidal mediator. The Nafion membrane derived from the self-assembled mesoporous Nafion–silica composites maintained the microstructures of the silica framework, which was confirmed by small angle X-ray scattering (SAXS) and TEM. The in situ time-resolved synchrotron SAXS clearly indicates that the presence of silica colloids is critical for the formation of the highly ordered mesoporous structured phase in the precursor solution. The best results are observed on Nafion membranes with 2D-H structure in terms of proton conductivity and cell performance under reduced relative humidity (RH) conditions, achieving proton conductivities of 0.08, 0.062 and 0.038 S cm1 at 100, 40 and 0%RH, respectively. Moreover, the power output of the mesoporous Nafion membrane cells show a S-shaped dependence on RH and are stable under anhydrous conditions (i.e., 0% RH), demonstrating the outstanding high water retention capability of the mesoporous structure of the membranes.